The Effect of Parents Digital Literacy on Sharenting Practices and Children’s Privacy on Instagram - Rapikah Harnum; Janette Maria Pinariya (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M) Institut Bisnis dan Komunikasi LSPR, 2023)
The development of technology has given rise to various social media platforms, suxh as Instagram. Instagram offers numerous features to its users for content creation, such as Instagram stories, feeds, Instagram reels, and live Instagram. The use of social media is closely related to digital literacy skills. Social media has a significant impact on society, including changes in parenting patterns, known as